Evaluasi Dampak Program Optimalisasi Lahan (OPLA) dalam Budidaya Padi di Subak Selasih Desa Puhu Kecamatan Payangan Kabupaten Gianyar - CAHYADI, I MADE PROMETEO SEPTIA; PUTRA, I GEDE SETIAWAN ADI; WULANDIRA SDJ, A.A.A. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.3, Juli 2017, 2017)
Evaluation of the impact of the Land Optimization Program (OPLA) in Rice Cultivation at the Selasih Subak of Puhu Village, Sub-District of Payangan, Gianyar Regency Population in Indonesia keeps growing with growth rate around 1,38 per year. In the last two decades, the increase rate in national food production was unable to compensate the increase rate in food needs. This reflects in increase of food product import such as rice, corn and soybean. Optimization of agricultural land is an attempt to boost the utilization of agricultural land resources into farming lands for crops, horticulture and plantation through improvements and increase of land carrying capacity. The aim of the research is to identify the program impact evaluation on the course of Special Attempt "Upaya Khusus (UPSUS)" program particularly Land Optimization "Optimalisasi Lahan (OPLA) in Subak Selasih about the impact of OPLA program in terms of technical, economical and social aspects. The research was conducted in Subak Selasih, Puhu Village, Payangan District, Gianyar Regency. Population in Subak Selasih is 73 people. Sample selection uses simple random sampling. Respondents are 42 people. The result of the research showed that technical impact is in well category with achievement score of 3,86, economical impact is in medium category with achievement score of 3,31 and social impact is in well category with achievement score of 3,69. Based on the research result of land optimization program impact evaluation, members of community need to continue the OPLA program, use more organic fertilizer to minimize costs and interact with other farmers to gain knowledge.